The Role of LEO Satellites for the (Cyber)Security Policiesof Authoritarian States: The Case of Iran - Stachoń, Monika (Global Governance of Low Earth Orbit Satellites, 2025)
This article explores the strategic importance of low Earth orbit (LEO) satellites in the (cyber)security policies of authoritarian states, focusing on the case of Iran. It examines how space technologies—especially LEO satellites—have become essential tools for advancing national security goals, enhancing regime stability, and reducing dependence on foreign technologies. The study traces the evolution of Iran’s space program, highlighting its integration into broader efforts to achieve technological autonomy, support military and intelligence operations, and maintain internal control.Iran’s increasing deployment of LEO satellites reflects a shift from primarily scientific and environmental applications to dual-use and military objectives. These satellites support critical functions such as environmental monitoring, disaster management, surveillance, and cyber intelligence. They also provide the government with tools to monitor opposition activities, control public communications, and promote regime propaganda. Developing an independent satellite infrastructure strengthens Iran’s resilience to sanctions and its ability to operate outside international technological systems.The article situates these developments within the frameworks of international space law, cybersecurity norms, and global power competition. It shows how space has become a new domain of strategic rivalry, particularly for states seeking to assert their sovereignty and resist Western influence. Iran’s case illustrates how LEO satellite capabilities contribute to authoritarian resilience and strategic positioning in both regional and global contexts.